Reference Interval for Calcium among Libyan Healthy Individuals - Fatima Al Majdoup (AlQalam Journal of Medical and Applied Sciences, 2024)
The goal of this study was to determine the reference intervals (RIs) of calcium levels (Ca) in the blood of Libyan individuals. Blood samples were obtained from 120 healthy males and females through aseptic venipuncture. Informed consent was obtained prior to sample collection. Serum was extracted from the centrifuged samples and analyzed spectrophotometrically to determine calcium concentrations. The non-parametric percentile method was applied to establish the RIs of calcium, results showed the reference period is 7.8- 10.1 mg/dl. The study establishes RIs for serum calcium concentration between 7.8 mg/dl and 10.1 mg/dl in the Libyan population. These findings underscore the importance of developing geographically specific RIs, as RIs derived from manufacturer’s kits or other populations may not accurately reflect the unique characteristics of the Libyan population. The RIs identified in this study are more relevant and appropriate for the Libyan context. تهدف هذه الدراسة إلى تحديد الفئات المرجعية لمستويات الكالسيوم في الدم لدى الأفراد الليبيين، حيث لم يتم إجراء دراسات سابقة حول هذا الموضوع في ليبيا. تم الحصول على عينات دم من 120 فردًا ليبيًا، تم استخلاص المصل وتحليله طيفياً لتحديد تركيز الكالسيوم. تم تطبيق طريقة النسبة المئوية غير البارامترية لتحديد الفئات المرجعية للكالسيوم، وكانت النتائج بين 7.8-10.1 ملغ/ديسيلتر. توضح الدراسة الفئات المرجعية لتركيز الكالسيوم في المصل بين 7.8 ملغ/ديسيلتر و 10.1 ملغ/ديسيلتر لدى السكان الليبيين. تشدد هذه النتائج على أهمية تطوير فئات مرجعية محددة جغرافياً، حيث قد لا تعكس الفئات المرجعية المستمدة من مجموعات البيانات الأخرى الخصائص الفريدة للسكان الليبيين. وبالتالي، فإن الفئات المرجعية المحددة في هذه الدراسة أكثر ملاءمة للسياق الليبي